(3GdYGbHI hPcQ GdehJs - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3jHJOF Hbhdg PcQ eSde Hf GdMLGL QMeg Gddg ef MOjK CfS Hf eGdc bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B:- ( (3dGjJefjf CMOce GdehJ dVQ fRd Hg aEf cGf s
(3BNQgG (B:s
(3hfJHGYO efgG HbHGFM CYeGdfG Hefg hWhdg dGQH ZjQg hdG eYHhO ShGg fLR cJGH GdYGbHI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1437s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdESdGejs